PENDAMPINGAN DIGITALISASI UMKM, BRANDING DAN MANAJEMEN LAPORAN KEUANGAN DESA SUKARENDAH - Maulana, Akmal; Tazakka, Muhammad Adullah; Fitriana, Reva Helma; Millani, Aprilia; Ummah, Shopiyatul; Ikhsan, Maulana; Rahmayani, Ririn; Saputri, Salma Gusni; Ela, Ela; Ginting, Fajar Mediawan (LPPM Universitas Bina Bangsa, 2024)
The digitalization of Micro, Small, and Medium Enterprises (MSMEs) is a strategic step to strengthen local economies in the digital era. This article discusses the importance of adopting digital technology to market MSME products through official village platforms. Digitalization enables MSMEs to reach wider markets, enhance branding, and improve financial transparency and accountability. A case study in Sukarendah Village illustrates how a Community Service Program (CSP) successfully empowered MSME actors through training on digitalization, branding strategies, and financial management. This article highlights the importance of collaboration between communities, village governments, and students in supporting the sustainability of MSME digitalization. With the right approach, digital transformation can become a catalyst for sustainable local economic growth.